Interorganizational Coordination and Collaboration During the 2015 MERS-CoV Response in South Korea. (13th August 2021) - Kim, Yushim; Oh, Seong Soo; Ku, Minyoung; Byeon, Jihyun
ABSTRACT: Objectives: This study examined the way organizations were involved in the response to the Middle East Respiratory Syndrome Coronavirus (MERS-CoV, MERS) outbreak that occurred in Korea in 2015. Data and Methods: We collected organizational network data through a content analysis of online news articles and the government's white paper. Social network analysis was used to analyze the key organizations and their connections in crucial response tasks. Results: Three national health authorities (Central MERS Management Headquarters [CMMH], Korea Centers for Disease Control [KCDC], Ministry of Health and Welfare [MOHW]) led the response. CMMH, which did not appear in the government's response plans, played a significant role in all 3 networks. KCDC also was involved in all 3 networks, but was most prominent in the laboratory testing network. MOHW appeared only in the patient management network. Each health authority coordinated and collaborated with distinctive types of organizations in the networks, but unclear lines of responsibilities also were found. Conclusions: The study demonstrated that the roles and responsibilities of health authorities at the national level were fragmented and lacked clarity. Public health emergency preparedness must consider carefully the way to establish collaborative response systems.